2010
DOI: 10.7202/038903ar
|View full text |Cite
|
Sign up to set email alerts
|

Deictic Center Shifts in Literary Translation: the Spanish Translation of Nooteboom’s Het Volgende Verhaal

Abstract: In this article, we explore the phenomenon of deictic center shifts in literary translation, concentrating on the Spanish translation (La historia siguiente, 1992) of the Dutch novel Het volgende verhaal (1991 [The Following Story, 1993]). The empirical description focuses on lexical spatiotemporal markers and verbal tenses. We compare the source text and the target text in order to identify the translational shifts: we consider these shifts as textual traces of the translator’s interpretive process of resetti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Unlike Goethals and De Wilde (2009), the shifts in deixis in this study seem to be systematic and tend to reflect certain translational behaviours or processes. Moreover, unlike the findings of Mason and Şerban (2003)which point to "distancing" the target reader, the tendency towards a greater deictic anchorage in the translated text can be indicative of a more emphasized and involved narrator which is most probably suggestive of a more emotionally-involved and approximated reader.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Unlike Goethals and De Wilde (2009), the shifts in deixis in this study seem to be systematic and tend to reflect certain translational behaviours or processes. Moreover, unlike the findings of Mason and Şerban (2003)which point to "distancing" the target reader, the tendency towards a greater deictic anchorage in the translated text can be indicative of a more emphasized and involved narrator which is most probably suggestive of a more emotionally-involved and approximated reader.…”
Section: Resultsmentioning
confidence: 62%
“…The study has focused only on the addition of person deictics that occurs as a result of (i) replacing a definite/indefinite article or a demonstrative with a person deictic (such as when translating "a/the/this horse" into "his horse"), and (ii) changing from passive to active voice in translation (such as when translating "the house was evacuated" into "we evacuated the house"). Goethals and De Wilde (2009), in a Dutch-Spanish translated novel, find that these translational deictic shifts are infrequent and unsystematic and therefore may not be related to an intentional translational choice. Goethals and De Wilde point out that that these shifts may be better seen as "traces of the translator"s cognitive deictic center shift, i.e.…”
Section: Deixis In Translation Studiesmentioning
confidence: 87%
See 1 more Smart Citation
“…The translational shifts are presumably local decisions, and in this sense they might reveal interesting local deictic center shifts, and as such can be interpreted as traces of the translator's interpreting and recontextualization effort. As was claimed by Goethals & De Wilde (2009), the search and the translational rendering of the deictic center clearly forms a constant threat to translators, and this difficulty can help explain the relatively high frequency of shifts in deictic expressions. It does not, however, allow to predict the form that the shifts will take: from demonstrative to definite or vice versa.…”
Section: Perceptual Frame Variationmentioning
confidence: 99%
“…These subtle contrastive differences are difficult to pinpoint solely on the basis of typological data, grammaticality judgments or monolingual corpus research (Cysouw and Wälchli 2007: 99;Dixon 2003;Johansson 2007;Wälchli 2007;Wu 2004: 23). From a translation theoretical point of view, it has been found that the shifts in the demonstrative paradigm are very frequent, and can be linked to the narratological characteristics of translations (Cuenca and Ribera 2011;Jonasson 2001;Mason and Şerban 2003) and the role of demonstratives in identifying the deictic center (Goethals and De Wilde 2009;Himmelmann 1996;Kleiber 2003;Philippe 1998). Although in Section 4, I will describe several groups of examples that illustrate the role of the translation process, the main focus will be the contrastive perspective (Section 5), looking at translational data as a heuristic tool to describe contrastive differences between Dutch and Spanish.…”
mentioning
confidence: 99%